2012
DOI: 10.2527/jas.2011-4112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein content and source on colonic fermentative activity in dogs differing in body size and digestive tolerance1

Abstract: Low-consistency, high-moisture feces have been observed in large dogs (Canis lupus familiaris), compared with small dogs, and particularly in sensitive breeds (e.g., German Shepherd dogs). The aim of this work was to determine if greater colonic protein fermentation is responsible for poorer fecal quality in large sensitive dogs. Twenty-seven bitches were allotted to 4 groups based on size and digestive sensitivity: small, medium, large tolerant, and large sensitive. Five experimental diets varying in protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 26 publications
7
39
0
Order By: Relevance
“…Several specificities in the composition of SENSI versus ADULT could explain its better results obtained in the present study. As observed by Nery et al [17], the higher the protein content (from 22 to 39% DM), the greater was the faecal score and the higher was the faecal fermentation [15,17]. In our study, the reduction of the protein content in SENSI vs ADULT (32 vs 39% DM) may have resulted in the normalization of faecal moisture and consistency as well as the reduction of fetid odours.…”
Section: Journal Of Veterinary Medicine and Surgery Issn 2574-2868supporting
confidence: 79%
See 1 more Smart Citation
“…Several specificities in the composition of SENSI versus ADULT could explain its better results obtained in the present study. As observed by Nery et al [17], the higher the protein content (from 22 to 39% DM), the greater was the faecal score and the higher was the faecal fermentation [15,17]. In our study, the reduction of the protein content in SENSI vs ADULT (32 vs 39% DM) may have resulted in the normalization of faecal moisture and consistency as well as the reduction of fetid odours.…”
Section: Journal Of Veterinary Medicine and Surgery Issn 2574-2868supporting
confidence: 79%
“…However, large dogs, and more specifically certain sensitive breeds such as German Shepherd, Labrador Retrievers, Great Danes or Giant Schnauzers, are known to have particularly sensitive digestive systems that are manifested by exacerbated colonic fermentations and lower faecal consistency [13][14][15][16][17][18], and whatever the breed, some individual dogs may also have digestive sensitivity without there being a specific cause. While a diet formulated with highly digestible proteins improves faecal quality in dogs, especially in large sensitive ones [15,17,18], increased dietary protein concentrations are suspected to lead to a greater faecal score by affecting the quantity of substrate available for colonic fermentation [15,18].…”
Section: Efficacy and Tolerance Of Two Lowcarbohydrate Diets In Largementioning
confidence: 99%
“…The influence of diarrhoea is therefore not directly reflected in our data, and might explain why Clostridium perfringens was not significantly increased by the HMB diet. Anyhow, the increased amount of isovaleric acid and pH in faecal samples of dogs fed HMB compared to CD1 and CD2, indicates that undigested proteins may reach the colon in at least some dogs consuming higher levels of proteins [20], and the proteolytic activities of bacteria may lead to increased levels of potentially detrimental metabolites. The implications for dog health are currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that the final products of bacterial fermentation mostly depend on the chemical composition of the chyme that reaches the large intestine [2,3]. For instance, if there is a lack of carbohydrates (e.g., wheat, maize) in the diet, the microorganisms ferment amino acids into short-chain fatty acids (SCFAs) and ammonia to obtain energy [4]. A sufficient throughput of carbohydrate leads to a decrease in luminal nitrogenous compounds and an increase in faecal bacterial mass [5].…”
Section: Introductionmentioning
confidence: 99%